Structural Equation Modeling Partial Least Square for Modeling the Relationship of Readiness, Creativity and Motivation to Students' Problem-Solving Ability - Mohamad Amin Lasaiba; Djamila Lasaiba; Arman Man Arfa; Irvan Lasaiba (research, training and philanthropy institution Natural Aceh, 2023)
This study aims to determine how much influence readiness, creativity, and learning motivation have on problem-solving abilities. This study used a quantitative approach and was conducted in class X SMA Negeri 13 Ambon with 41 students selected by purposive sampling. Tests and questionnaires were used in data collection and analyzed with SMART PLS 4. The results showed that the external model loading factor and Cronbach's Alpha > 0.7 had high validity and reliability. The campaign, creativity, and motivation variables of 54.6% can explain the inner model of the dependent variable. Furthermore, for the hypothesis, there is a positive and significant effect of the readiness and motivation variables, while creativity has no effect and is not substantial. This research has implications for increasing students' cognitive readiness independently through motivation to develop creative ideas and connect the knowledge gained in solving problems